Cardiogenic Shock From Heart Failure Versus Acute Myocardial Infarction: Clinical Characteristics, Hospital Course, and 1-Year Outcomes. (5th May 2022) - Sinha, Shashank S.; Rosner, Carolyn M.; Tehrani, Behnam N.; Maini, Aneel; Truesdell, Alexander G.; Lee, Seiyon Ben; Bagchi, Pramita; Cameron, James; Damluji, Abdulla A.; Desai, Mehul; Desai, Shashank S.; Epps, Kelly C.; et al.
Abstract : Background: Little is known about clinical characteristics, hospital course, and longitudinal outcomes of patients with cardiogenic shock (CS) related to heart failure (HF-CS) compared to acute myocardial infarction (AMI; CS related to AMI [AMI-CS]). Methods: We examined in-hospital and 1-year outcomes of 520 (219 AMI-CS, 301 HF-CS) consecutive patients with CS (January 3, 2017–December 31, 2019) in a single-center registry. Results: Mean age was 61.5±13.5 years, 71% were male, 22% were Black patients, and 63% had chronic kidney disease. The HF-CS cohort was younger (58.5 versus 65.6 years, P <0.001), had fewer cardiac arrests (15.9% versus 35.2%, P <0.001), less vasopressor utilization (61.8% versus 82.2%, P <0.001), higher pulmonary artery pulsatility index (2.14 versus 1.51, P <0.01), lower cardiac power output (0.64 versus 0.77 W, P <0.01) and higher pulmonary capillary wedge pressure (25.4 versus 22.2 mm Hg, P <0.001) than patients with AMI-CS. Patients with HF-CS received less temporary mechanical circulatory support (34.9% versus 76.3% P <0.001) and experienced lower rates of major bleeding (17.3% versus 26.0%, P= 0.02) and in-hospital mortality (23.9% versus 39.3%, P <0.001). Postdischarge, 133 AMI-CS and 229 patients with HF-CS experienced similar rates of 30-day readmission (19.5% versus 24.5%, P =0.30) and major adverse cardiac and cerebrovascular events (23.3% versus 28.8%, P =0.45). Patients with HF-CS had lower 1-year mortality (n=123, 42.6%) compared to the patients with AMI-CS (n=110, 52.9%, P =0.03). Cumulative 1-year mortality was also lower in patients with HF-CS (log-rank test, P =0.04). Conclusions: Patients with HF-CS were younger, and despite lower cardiac power output and higher pulmonary capillary wedge pressure, less likely to receive vasopressors or temporary mechanical circulatory support. Although patients with HF-CS had lower in-hospital and 1-year mortality, both cohorts experienced similarly high rates of postdischarge major adverse cardiovascular and cerebrovascular events and 30-day readmission, highlighting that both cohorts warrant careful long-term follow-up. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03378739.